Networks of scientific collaboration in the historiographic research of psychology in Latin America - Cudina, Jean Nikola; Ossa, Julio César; Jacó-Vilela, Ana Maria (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
This study aims to carry out an analysis of the scientific collaboration networks that are organized from the development of historiographical research in psychology in Latin America. For this purpose, the empirical corpus is the academic production of researchers who are members of the Rede Iberoamericana de Pesquisadores em História da Psicología (RIPeHP) [Iberoamerican Network of Researchers in Psychology History]. Bibliometric tools are used to map the networks and establish indicators of scientific collaboration. Specifically, co-authorship analysis is used to identify the visible and hidden academic communities that are formed from the dynamics of historiographical research in the region. The creation of the Network was made possible in part by the initiative of researchers from the history working group of the Interamerican Society of Psychology (SIP). This year the SIP celebrates seventy years of history since its creation in 1951. In the case of this study, we present information relevant to historiographical research and discuss the role of the SIP in promoting and contributing to the strengthening of the history of Latin American psychology